Inclusione: un possibile principio guida per la psichiatria sociale? - Homberg, Annelore; Wunder, Michael (Il sogno della farfalla, 2017)
Inclusion is neither a synonym of integration nor does it replace the latter. The term integration refers to an irreversible social process which, at the time being, is far from being achieved. On the contrary, the concept of inclusion suggests a multifaceted society which is made of several different subsystems and draws its dynamicity from coexisting differences. This aim has not been achieved either. How relevant is the concept of inclusion for social psychiatry? Can we assume that inclusion has always been a keyword for social psychiatry although this has never been overtly declared? By starting from wondering whether territorial services for mental health should be characterized by generalization or by specialisation and discussing the difference between the two German terms Betreuung (taking care) and Assistenz (provision of services), the author shows how the concept of inclusion may support the development of social psychiatry.